Hubungan Pengetahuan Ibu Hamil Tentang Tanda Tanda Bahaya Kehamilan Dengan Jumlah Kunjungan Pemeriksaan Antenatal Care (ANC) di Puskesmas Sukajadi Kota Prabumulih - Titik Almujahidiani, Rini Mayasari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
ABSTRACT Antenatal Care (ANC) is a health service for pregnant women during their pregnancy with the aim of early detecting problems with maternal and fetal health, providing health education and planning for childbirth so that they can face childbirth safely. This research aims to determine the relationship between pregnant women's knowledge about danger signs of pregnancy and the number of antenatal care (ANC) visits. This research is a quantitative study with a cross sectional approach. The sample amounted to 50 respondents, sampling using purposive sampling technique with chi square statistical test analysis with a significant level of α (0.05). The results showed that 32 respondents had good knowledge and 18 respondents had sufficient knowledge, 32 respondents had ANC inspection visits that complied with the rules and 18 respondents did not comply with the rules. The statistical test results obtained a p value of 0.000 so that it can be concluded that there is a relationship between pregnant women's knowledge about danger signs of pregnancy and the number of visits for antenatal care (ANC) examinations at the Sukajadi Health Center, Prabumulih city. Keywords: Antenatal Care, Knowledge, Danger Signs of Pregnancy.